Proposta de manual técnico para elaboração de um programa de monitoramento da qualidade da água subterrânea no estado do Pará - SIQUEIRA, Maria Roberta Cavalcante de (Universidade Federal do Pará, 2024)
Monitoring groundwater is an extremely important activity for diagnosing and controlling potentially polluting activities. Applied to environmental management and control, whether due to a requirement from the regulatory body, through environmental license conditions, it represents a major environmental liability for companies that are not meeting the requirements demanded by these respective regulatory bodies. Activities that can cause changes in groundwater require periodic monitoring to ensure the maintenance of environmental quality, as they are standardized and require standards, manuals and regulations. This respective manual was conducted based on standards from the Brazilian Association of Technical Standards ABNT), international legislation, monitoring manuals and solutions on water quality applicable to the topic, as well as collections made up of monitoring wells within the Campus of the Federal University of Pará, in Belém (experimental area of this research). To this end, disposable Bailer samplers and measurements were used using the low flow system, aiming to define clear guidelines and rules for carrying out the activities involved in the process, as well as commenting on other devices that could be used for collection. of groundwater samples. At the end, a manual of good practices was proposed as a way of ordering and guiding the groundwater monitoring process. It is expected that this proposed technical manual will serve as a reference for groundwater collection, as given the concern within the State of Pará, it is extremely important to organize effective action and forward solutions to this environmental problem. Additionally, this manual is intended to be a purposeful document, and can be useful in environmental monitoring in different polluting activities.